An Analysis of Mosque Financial Transparency through Announcement of Infaqand Sodaqohwith Mosque Toa at Friday Prayers - Hasanah, Rofidatul; Farid, Achmad (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2024)
Purpose: to analyse mosque financial transparency practices focusing on announcing the receipt and use of infaq and sadaqah to Friday prayer congregations using mosque toa. Methodology: This research uses a type of qualitative method with a descriptive approach to explore and understand the practice of mosque financial transparency through the announcement of infaq and sadaqah to Friday prayer congregations at the Jami' Al Huda Mosque Banjarejo Gunungsari District Umbulsari Jember Regency. Data were collected through participant observation, in-depth interviews, and document analysis. Findings: This practice of announcing management and infaq and sadaqah not only increases the accountability of mosque administrators but also strengthens the congregation's trust in fund management, which is carried out openly and clearly. Apart from building trust, financial report announcements also positively impact congregational solidarity. Congregants feel more involved and have a sense of shared responsibility, reflected in increased financial contributions and participation in religious activities. However, challenges such as time constraints were noted. Novelty: This study contributes to the literature by explicitly examining the role of sound reinforcement or toa in increasing mosque financial transparency and cultural factors in encouraging financial transparency.